Nilai Pendidikan Islam Tentang Keadilan dalam Perspektif Al Qur'an Surat Al Hujurat Ayat 9 - Udiyono Udiyono; Robingun Suyud El Syam; Vava Imam Agus Faisal (Pusdikra Publishing, 2025)
This study aims to: (1) analyze the concept of justice in the perspective of the Qur’an, particularly in Surah Al-Hujurat verse 9, as interpreted by classical and contemporary mufassirun; (2) identify the values of Islamic education related to justice embedded in the verse; (3) explain the relevance of these educational values to educational practices in Indonesia; and (4) describe the implementation of the value of justice in Islamic educational institutions in Indonesia. This research employs a qualitative approach using a library research method, drawing upon Qur’anic exegesis (tafsir), Islamic education literature, and modern educational studies. The findings indicate that mufassirun such as Ibn Kathir, Al-Tabari, and M. Quraish Shihab emphasize that Surah Al-Hujurat verse 9 commands the fair, objective, and impartial resolution of conflicts among Muslim groups. Justice in this verse is viewed as a manifestation of Allah’s attribute Al-‘Adl, making human justice a reflection of divine values. The mufassirun assert that the guidance of this verse is not limited to large-scale conflicts but is also applicable to social, familial, organizational, and educational contexts. The Islamic educational values derived from the verse include deliberation (shura), reconciliation (islah), honesty, objectivity, social responsibility, and the enforcement of justice. These values are highly relevant to Indonesia’s national education principles, particularly those emphasizing character education, non-violence, and a culture of peace. The implementation of justice values in Islamic educational institutions is reflected in character-based curricula, institutional governance, disciplinary policies, and teacher training in conflict management. Surah Al-Hujurat verse 9 contains fundamental Islamic educational values, including justice (al-‘adl), social responsibility, peace-building, anti-violence (anti-bullying), truth enforcement, dialogue and deliberation, and brotherhood (ukhuwwah). These values serve as a moral and ethical foundation for Islamic education in shaping learners who are just, peaceful, and civilized. The study concludes that the values of justice articulated in the verse are strongly relevant to educational practices in Indonesia, particularly in strengthening character education, managing school conflicts, fostering an equitable and anti-bullying school culture, developing value-based curricula, and nurturing teachers as role models of justice and professionalism. The study recommends strengthening justice-oriented policies in Islamic educational institutions, enhancing teachers’ competencies in conflict resolution, expanding future research on practical implementations of justice values, and utilizing these findings as a reference for formulating value-based educational policies.